Partial observability of stochastic semilinear systems - Bashirov, Agamirza E.; Ahmadova, Arzu (Elsevier, 2022)
In this article, we consider an Ito stochastic semilinear differential equation with unknown initial state and a linear observation system. It is proved that under a certain condition on the observability Gramian, the initial state of the equation can be recovered. This result is demonstrated by an example. (C) 2022 Elsevier B.V. All rights reserved.
Keywords: Stochastic system; Semilinear system; Partial observability; Observability Gramian